(untitled) (Palíndromo, 2013)
This article is an excerpt from a previous research, concluded in 2009, in which are presented reflections in relation to the educational role of museums and educational practices, based on some official documents that determine an educational policy for the museum spaces, as on studies of authors who investigate education in museums. In addition, it presents an analysis of some issues that permeate the educational actions in Brazilian art museums.